A Study on Customer Preference Towards Customs Clearance Agency - Manikandan A; P. Sudha; V. Pradeep (Research Parks Publishers, 2023)
The results of this research will aid the firm in better understanding its clientele. A country's customs department is the government agency in charge of regulating the entry and exit of various products, including animals, vehicles, people, and potentially dangerous materials. Customs has traditionally been thought of as the fiscal topic responsible for levying tariffs and other taxes on imported and exported goods. Over the past few decades, there has been a widespread expansion of perspectives on customs functions, which today encompass taxation, security, and trade facilitation. The customs authorities of each country strictly enforce their own set of laws and regulations regarding the import and export of products, and some items may be prohibited from entering or leaving the country altogether. Those who disobey these laws are subject to a variety of punishments. The Indian customs compliance information portal was recently released by the Indian customs authorities with information on customs procedures and regulatory compliances for import-export commerce. The article provides a concise overview of the important import-export procedures in India, as well as the many promotional schemes and activities now being done to aid exporters. There are more than 200 people in the population. Convenience sampling was used to collect data, and Chi-square and the f-test were employed to analyse the data for two-sample variance. Customers' preferences for freight forwarders and customs brokers are analysed using graphical tools like bar charts and pie charts. Freight forwarders are businesses that mediate between the shipper and the transportation company. Today's freight forwarders do more than just plan shipments, prepare paperwork, organise storage, and help with customs clearance on behalf of shippers and importers. The article aspires to defend the value of freight forwarders by highlighting their contributions to society and the economy.